Impact of pathological complete response following neoadjuvant chemotherapy (gemcitabine, nab-paclitaxel, S-1) and radiation for borderline resectable pancreatic cancer: a case report and review of literature - Mitsuru Kinoshita; Sota Watanabe; Gaku Mizojiri; Akitada Sada; Hiroki Kai; Yasunori Masuike; Yoshinobu Nagasawa; Kentaro Maruyama; Kyowon Lee; Mai Ohata; Osamu Ishikawa; Hiroshi Oka (Surgical Case Reports)
Abstract Background Pancreatic cancer (PC) is a highly lethal malignancy, even if surgical resection is possible (median survival: < 30 months). The prognosis of borderline resectable pancreatic cancer (BR-PC) is even worse. There is no clear consensus on the optimal treatment strategy, including pre/postoperative therapy, for BR-PC. We report a patient with BR-PC who achieved clinical partial response with neoadjuvant chemoradiation therapy (NACRT) and underwent curative resection, resulting in pathological complete response (pCR). Case presentation A 71-year-old man with jaundice and liver dysfunction was referred to our department because of a 48-mm hypo-vascular mass in the pancreatic head with obstruction of the pancreatic and bile ducts and infiltration of superior mesenteric vein and portal vein. The lesion was identified as atypical cells which suggested adenocarcinoma by biopsy, and he was administered NACRT: gemcitabine and nab-paclitaxel, following S-1 and intensity modulated radiation therapy. After reduction in the tumor size (clinical partial response), pancreaticoduodenectomy was performed, and pCR achieved. Postoperative adjuvant chemotherapy with S-1 was initially administered and the patient is currently alive with no recurrence as of 2 years after surgery. Conclusions NACRT is a potentially useful treatment for BR-PC that may lead to pCR and help improve prognosis.